Management of tax system of Kazakhstan and Russia: comparative experience - Omarova, A.T.; Grelo, M.F.; Kamenova, М.Zh. (KSU Publ., 2018)
The article is devoted to the problem of reforming the tax systems of Kazakhstan and Russia in a market economy; the main key steps and the quality of their realizations are described. Of particular relevance is the analysis of the impact of tax regulators on the country's economic growth. In the context of integration into the world economy, it is necessary to find the most appropriate scientific approaches to reforming tax systems by improving the analysis, planning and forecasting the trends of its development, taking into account the influence of various factors. As the analysis of the works of foreign scientists in forecasting the development of complex financial systems in the conditions of a modern market economy shows, it is the methodology of alternative forecast scenarios that reflects the needs of strategic foresight in the context of a complex intertwining of contradictory trends in the development of the world economy. It is generally recognized that in the context of rapid and ambiguous changes, it is no longer possible to use planning methods based solely on extrapolating existing trends in technical, technological, economic and social development. Therefore, it is important to compare the state of tax systems to date and assess their level of competitiveness. Regarding Kazakhstan and Russia, the results of the regression model should be taken into account when carrying out reforms. The model of the tax system is an aggregate indicator, the so-called tax policy, so only a systemic transformation will help to qualitatively influence the economic growth of the country.
Қазақстанның жəне Ресейдің салық жүйелерін басқару: салыстырмалы тəжірибе
Управление налоговыми системами Казахстана и России: сравнительный опыт
Keywords: management; tax systems; reform of tax systems; regression analysis; fiscal instruments; economic growth; tax breaks; tax rebate; tax holidays; forecast